Optimalisasi Literasi Informasi Siswa SMP Negeri 5 Lamongan melalui Kegiatan Workshop Pengarang Cilik - Hadi, Wiwin Puspita; Rosyiidah, Wihdah Salsabiila; Brilyansyah, Daffa Addin; Sirajudin, Muhammad Hafid; Hermawanti, Ninis Zeni Dwi; Maulidda, Sri Wahyuniati; Rahayu, Eni Puji (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Information literacy is essential for students to select, criticize, evaluate, and use information so they can be careful. This service activity aims to increase student information literacy and implement information literacy to produce a written work and be published in book form so that it can be disseminated to motivate other students. Community service activities were held at SMP Negeri 5 Lamongan, East Java. The target group is students who have high motivation for writing. Service activities consist of (1) the preparatory stage, which consists of observation, interviews, and identification of needs, (2) the implementation stage, which consists of observation, interviews, and identification of needs, (2) the implementation stage, which consists of writing seminars, monitoring, and collecting the products, (3) the monitoring stage; and (4) evaluation stage. The results of the service show that students' information literacy increases, and students can produce works that have been recorded and can be disseminated. It is hoped that this activity will be carried out consistently so that it can help students improve their information literacy skills to become great writers in the future.